An investigation of microstructure and properties of Sn3.0Ag0.5Cu-XAl2O3 composite solder. Issue 2 (4th April 2016) - Chen, Guang; Huang, Bomin; Liu, Hui; Chan, Y.C.; Tang, Zirong; Wu, Fengshun
Abstract : Purpose: The purpose of this paper is to investigate microstructure and properties of Sn3.0Ag0.5Cu-XAl2 O3 composite solder which were prepared through powder metallurgy route. Design/methodology/approach: Sn3.0Ag0.5Cu (SAC305)-XAl2 O3 (X = 0.2, 0.4, 0.6, 0.8 Wt. %) composite solders were prepared through the powder metallurgy route. The morphology of composite solder powders which consists of Al2 O3 particles and SAC solder powders after ball milling was observed. The retained ratio of Al2 O3 nanoparticles in composite solder billets and solder joints were also quantitatively measured. Furthermore, the as-prepared composite solder alloys were studied extensively with regard to their microstructures, thermal property, wettability and mechanical properties. Findings: After ball milling, the Al2 O3 nanoparticles added were observed embedded into the surface of SAC solder powders. Only about 5-10 per cent of the initial Al2 O3 nanoparticles added were detected in the composite solder joints after reflow. In addition, finer ß-Sn grains were achieved with addition of Al2 O3 nanoparticles; the Al2 O3 nanoparticles were found retained in the composite solder matrix. Besides, negligible changes in melting temperature and the considerably reduced undercooling were obtained in composite solder alloys. Wettability was improved by appropriate addition of Al2 O3 nanoparticles. Microhardness and shear strength of composite solders were both improved after Al2 O3 nanoparticles addition. Originality/value: This paper indicated that powder metallurgy route offered a feasible approach to produce nanoparticle reinforced composite solder. In addition, the quantitative analysis of the actual retained ratio of the Al2 O3 nanoparticles in solder joints provided practical implications for the manufacture of composite solders.